Analisis Faktor Perubahan Kurs Rupiah Terhadap Valuta Asing: Systematis Literatur Review - Afina Khusna Mufidah; Arlian Sherly Anjani; Tasyanari Handayani; Erni Puji Astutik (Student Research Journal, 2023)
Exchange rate is the exchange rate of one country's currency with another country's currency which is carried out for international transaction purposes. The demand and supply of a currency are influenced by several factors which will cause fluctuating changes in the exchange rate of a currency to another country's currency or foreign currency. This research aims to analyze the factors that influence changes in the rupiah exchange rate against foreign currencies. The method used in this research is a systematic literature review which will dig deeper by observing, reviewing, presenting, and interpreting research, with data taken from Google Scholar and Sinta literature. The research results show that the factors that influence changes in the rupiah exchange rate against foreign currencies are inflation, money supply, and interest rates.